Developing a conceptual framework for burnout intervention program in the workplace - Sundram, Bala Murali; Kumareswaran, Suriya (Universa Medicina, 2024)
This review proposes a comprehensive conceptual framework for developing and implementing burnout intervention programs in the workplace. In recent years, job burnout has become a new and vigorous research hotspot in the field of psychology and human resources management at home and abroad. Job burnout has a serious impact on personal health and performance but also harms the work efficiency, organizational effectiveness, and even social stability of employees. With the escalating concern over employee burnout and its consequent negative impacts on both individual health and organizational productivity, there is a pressing need for effective strategies to mitigate this issue. The framework draws on extensive literature review and theoretical model analysis, integrating key theories such as the Job Strain Model, Effort-Reward Imbalance Model, Conservation of Resources Theory, and the Job Demands-Resources Theory to explore the multifaceted nature of burnout. It identifies critical components of burnout, including symptoms such as emotional exhaustion, depersonalization, and reduced personal accomplishment, and contributing factors such as high job demands, inadequate job resources, and personal traits. Intervention strategies such as exercise have been identified as beneficial in addressing burnout. A systematic review of six studies highlights that aerobic exercise effectively lowers burnout and stress levels among employees. The framework also examines mediating factors such as personality traits and external factors, evaluating outcomes such as improved mental and physical health, enhanced job performance, and better workplace environment. Moreover, this review discusses the sustainability of interventions and emphasizes the importance of tailoring approaches to fit specific organizational contexts. The proposed framework provides a structured approach to understanding and addressing workplace burnout, highlighting the necessity for ongoing research and adaptation of intervention programs to meet evolving workplace dynamics.